Generation of Newtonian and non-Newtonian droplets in silicone oil flow by means of a micro cross-junction. (August 2018) - Rostami, Behnam; Morini, Gian Luca
Highlights: An analysis of the characteristics of Newtonian and non-Newtonian droplets obtained with a micro cross-junction is presented. Before the droplet pinch-off of shear thinning dispersed phases a long thread is formed. With shear thinning fluids jetting is not possible at large flow rate ratio and low Capillary numbers ( Cac  < 0.03). Mono-dispersed emulsions of Xanthan gum solutions can be obtained only in a restricted range of values of α and Cac with respect to water. An increase of the viscosity ratio is beneficial in order to obtain the transition from a droplet regime to another one for a fixed value of Cac and α . Abstract: In this paper the generation of non-Newtonian and Newtonian droplets in a continuous silicone oil flow through a micro cross-junction has been studied experimentally by focusing the attention on the behavior of the device at values of continuous Capillary number ( Cac ) larger than 0.01. Different liquids have been used as dispersed phase: (i) pure water; (ii) water with Tween 20; (iii) Xanthan gum aqueous solutions. A wide range of volumetric flow rates of the continuous and dispersed phase have been imposed at the inlets of the micro cross-junction with the aim to correlate the main droplet regimes (squeezing, dripping and jetting) to the continuous and dispersed Capillary number ( Cac, Cad ) and to the volumetric flow rate ratio ( α ). The role of the viscosity ratio of the immiscible liquids ( λ ) on the droplet regime is discussed. The experimental results confirm that the transition between squeezing and dripping depends mainly on the Capillary number associated to the continuous phase and not on the viscosity ratio. On the contrary, larger viscosity ratio values tend to reduce the Capillary number in correspondence of which the transition between dripping and jetting is observed. In addition, it has been observed that an increase in the viscosity of the dispersed phase tends to reduce the range of the operative conditions in correspondence of which monodispersed emulsions can be generated.